Conservation Farming System of Vegetable Crops in Upstream Areas of Subwatershed Cikapundung - Sutrisna, Nana; Oktorie, Olivia (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
The function change of land in upstream areas of subwatershed Cikapundung is very difficult to control. Most of the land has been turned into residential areas and vegetable crops. Land is currently a source of life, so it is exploited to get maximum results and income. If it is not managed properly, the land will be degraded and eventually become critical. In order for the land to be sustainable it needs an environmentally friendly farming farming system for vegetable conservation The results showed that there were two technologies for specific vegetable crop conservation systems in upstream areas of subwatershed Cikapungdung that were environmentally friendly, namely (1) Conservation farming system of bench terrace conservation, beds cutting slopes, using manure + lime, plastic mulch installed, planting system of intercropping/ overlapping rotating vegetables on land with slope of 15-25%. The conservation farming system is able to control erosion from 69.93 to 7.18 t/ha/year or by 89.73% and (2) a farming system for conservation of ridge terraces, beds cutting slopes, using manure + lime, installed plastic mulch, system for planting intercropping/overlapping vegetables on land with a slope of 8-15%. The conservation farming system is able to reduce erosion from 37.41 to 15.27 t/ha / year or 59.18%. The two conservative farming systems above are financially profitable as indicated by the value of BC Ratio> 1, NVP> 0, and IRR> The prevailing Social Discount Rate or Bank interest, which is around 12% indicated by the value of BC Ratio> 1, NVP > 0, and IRR> Current Social Discount Rate or Bank interest, which is around 12%.